2014
DOI: 10.1099/ijs.0.060780-0
|View full text |Cite
|
Sign up to set email alerts
|

Endozoicomonas atrinae sp. nov., isolated from the intestine of a comb pen shell Atrina pectinata

Abstract: Endozoicomonas atrinae sp. nov., isolated from the intestine of a comb pen shell Atrina pectinata A novel bacterium, designated strain WP70 T , was isolated from the gut of a comb pen shell (Atrina pectinata) collected from the southern sea of Yeosu in Korea. The isolate was Gram-stainnegative, aerobic, non-motile and rod-shaped. Phylogenetic analyses based on 16S rRNA gene sequences indicated that strain WP70 T belonged to the genus Endozoicomonas. The highest level of sequence similarity (98.4 %) was shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 33 publications
0
35
1
1
Order By: Relevance
“…To our knowledge, this is the first report of Endozoicomonaceae occupying a large proportion of the fish gut microbiome. Bacteria of this family, within the widely distributed Oceanospiralles group, exhibit diverse heterotrophic metabolisms (Neave et al, 2014) and are commonly identified as symbionts in marine invertebrates (Bayer et al, 2013a; Bayer et al, 2013b; Forget & Kim Juniper, 2013; Nishijima et al, 2013; Beinart et al, 2014; Hyun et al, 2014), suggesting invertebrate prey as a potential vector of transport into the fish microbiome. The functional properties and potential for long-term residency of these bacteria in reef fishes remain to be verified.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first report of Endozoicomonaceae occupying a large proportion of the fish gut microbiome. Bacteria of this family, within the widely distributed Oceanospiralles group, exhibit diverse heterotrophic metabolisms (Neave et al, 2014) and are commonly identified as symbionts in marine invertebrates (Bayer et al, 2013a; Bayer et al, 2013b; Forget & Kim Juniper, 2013; Nishijima et al, 2013; Beinart et al, 2014; Hyun et al, 2014), suggesting invertebrate prey as a potential vector of transport into the fish microbiome. The functional properties and potential for long-term residency of these bacteria in reef fishes remain to be verified.…”
Section: Resultsmentioning
confidence: 99%
“…More generally, Endozoicomonas are commonly assumed to provide an important role in coral holobiont functioning due to their widespread prevalence and high abundance in many coral species (Bayer et al., 2013; Gignoux‐Wolfsohn, Aronson, & Vollmer, 2017; Glasl et al., 2016; Jessen et al., 2013; Meyer, Gunasekera, Scott, Paul, & Teplitski, 2016; Neave et al., 2016; Neave, Rachmawati, et al., 2017) and apparent metabolic versatility (Ding, Shiu, Chen, Chiang, & Tang, 2016; Hyun et al., 2014; Neave, Michell, et al., 2017; Yang et al., 2010). Further, reductions in the abundance of Endozoicomonas in stressed, diseased, or bleached corals are reported in a number of studies, suggesting that pervasive abundance of Endozoicomonas might be an indicator of habitat suitability (Bourne et al., 2008; Cárdenas et al., 2012; Gignoux‐Wolfsohn et al., 2017; Meyer et al., 2016; Morrow et al., 2014; Roder et al., 2015; Röthig et al., 2016; Ziegler et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…( Gammaproteobacteria ; Oceanospirillales ) are dominant members of the bacterial community associated with diverse marine invertebrates, including corals (16), sponges (7), gorgonians (8, 9), molluscs (1013), and tubeworms (14), as well as a basal chordate (15). In some hosts, these bacteria have been observed intracellularly (2, 11, 13).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Clarifying the functional capabilities of Endozoicomonas has been challenging because they reside in or on a host organism and can be difficult to culture (6). Only a handful of isolates are available in culture collections (7, 10, 12, 18, 19). Thus, metagenomic or single-cell analyses may be useful techniques for assessing the genomic capabilities of these bacteria; however, a lack of genetic resources hampers these approaches.…”
Section: Genome Announcementmentioning
confidence: 99%